PSXVII-16 Effect of hair characteristics on vaginal temperature under hot and humid conditions in an Angus-Brahman multibreed herd. (7th December 2018) - Sarlo Davila, K; Hamblen, H; Hansen, P; Dikmen, S; Elzo, M; Mateescu, R
Abstract: Thermal stress is a major limiting factor of production efficiency in beef cattle. Thermal tolerance is influenced by many factors, including breed and hair coat properties. In 2017, vaginal temperature was measured at 5-min intervals for 5 days in 113 heifers from the multibreed herd (ranging from 100% Angus to 100% Brahman) of the University of Florida. Ambient environmental conditions monitored using HOBO data loggers were used to calculate a temperature humidity index (THI). The coat score was scored as 1 = very smooth, 2 = smooth, 3 = long, and 4 = wooly. Hair samples were measured for length and diameter using ImageJ software. Vaginal temperatures during low and high THI were evaluated using generalized linear models with breed group and coat score as fixed effects. Hair length (long, short and overall) was different among the breed groups with the 100% Brahman group having the shortest hair. During low THI breed composition, coat score, average hair length, short hair length and long hair length were found to have significant effects ( P < 0.05) on vaginal temperature. During high THI only long hair length ( P = 0.0518), short hair length ( P = 0.0560) and average hair length ( P = 0.0587) were found to have significant effects on vaginal temperature. Hair diameter was not found to have an effect on vaginal temperature at either THI status. Table 1 shows the least squares means of short, long and average hair lengths relative to breed composition. Hair length across all three measurement tends to decrease as Brahman percentage increases. While both breed composition and hair characteristics influence vaginal temperature under hot, humid conditions, breed composition also influences hair characteristics.